Protein Content Analysis of the Giant Mottled Eel (Anguilla marmorata) from Lake Talaga and Its Development as a Flipbook Learning Medium - Syudur, Misbahun; Dhafir, Fatmah; Ashari, Abdul; Masrianih; Rafiqah; Trianto, Manap (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to analyze the protein content of Anguilla marmorata collected from Lake Talaga, Dampelas District, Donggala Regency, and to explore its potential for development as a learning medium. A descriptive quantitative approach was employed. Protein content was determined using the Biuret method coupled with UV–Vis spectrophotometry, with Bovine Serum Albumin (BSA) used as the standard. The protein contents obtained from three replicate measurements were 19.61%, 19.37%, and 20.43%, respectively, with a mean value of 19.80% and a range of 19.37–20.43%. These results indicate that the analyzed A. marmorata sample had a relatively high protein content, with consistent values across replicate measurements. The feasibility assessment of the developed flipbook yielded an overall mean score of 87.85%, corresponding to the “highly feasible” category. The content expert, media expert, and design expert assessments were 92.5%, 78.5%, and 88.0%, respectively, while the student response score was 92.4%. Overall, this study provides preliminary information on the protein content of A. marmorata from Lake Talaga and demonstrates the potential of the research findings to be integrated into a flipbook as a contextual learning resource for biology and nutrition-related topics.